Electrochemical Reduction and Deposition of Reduced Graphene Oxide/Manganese Oxide Composite for Supercapacitor Applications via Pulse-Chronoamperometry - Lakshmi Gandhan, Jaya Senan; Chen, Lim Tay; Suh, Cem Pang; Suk, Fun Chin (UTHM Publisher, 2017)
The reduced graphene oxide/manganese oxide composite was deposited on the nickel current collector using the Pulse-Chronoamperometry method in a mixture of graphene oxide dispersion and manganese acetate as the precursor. The graphene oxide (GO) was electrochemically reduced to reduced graphene oxide (rGO) and deposited with manganese oxide (MnOx) at the same time. The effects of manganese acetate (Mn(Ac)2) concentration, deposition temperature, voltage and time on the specific capacitance of rGO/MnOx electrode were investigated. The electrochemical properties were characterized using galvanostatic charge-discharge and cyclic voltammetry. The effects of electrochemical reduction and deposition parameters on the specific capacitance of rGO/MnOx electrode were studied using Central Composite Design methodology and a 2 factors interaction model equation was evaluated. The rGO/MnOx electrode synthesized using 0.2 M of Mn(Ac)2, at 70 °C and -1.0 V versus Saturated Calomel Electrode (SCE) with a total deposition time of 800s exhibited a specific capacitance of 665 F/g was obtained at the current density of 5 A/g. The high specific capacitance of rGO/MnOx electrode showed its potential application for the fabrication of supercapacitors. This study provides an environmental friendly, time effective and costs efficiency way to reduce graphene oxide and to deposit the rGO/MnOx composite for electrochemical energy storage application.